Women Empowerment through Self Help Groups: Case Study in Jalandhar District of Punjab - Kaur, Lakhwinder; Sachan, Divya; Sulibhavimath, Arjun (International Journal of Bio-resource and Stress Management, 2017)
Rural women today have been suffering a lot due to the feeling of helplessness and lack of decision-making capabilities in financial matters. Self-help groups (SHGs) are the most recent development for them which could enable them to come forward and make them self-dependent and self-employed. The present study was conducted in Jalandhar district of Punjab state in 2014 by focused on in-depth study of two groups i.e., Mian mamli and Nari shakti formed by Pahal NGO. The present study revealed that on an average fifty per cent of the members were young, matriculates, labourers, belonged to SC category, earned up to sixty five thousand per annum. Majority of the women (>90%) joined the group for a variety of reasons like to supplement family income, to develop social ties, to avail economic benefit, to develop habit of savings and to get easy access for credit which resulted in increased their income and savings. The study further revealed that majority of the members of self-help groups participated in various training programmes organized by promoting agency and Krishi Vigyan Kendra as a result of which women who never used to step outside the four walls of their home became business women and started supplementing their family income by adopting various entrepreneurial activities viz. candle and surf making, pickle formation and processing of fruits and vegetables etc.